Rising atmospheric CO2 levels result in an earlier cyanobacterial bloom-maintenance phase with higher algal biomass - Wang, Peifang; Ma, Jingjie; Wang, Xun; Tan, Qingqian (Water research (Oxford), 2020)
•We study the pCO2 spatiotemporal variability in lake taihu from 2006 to 2016.•The pCO2-undersaturated areas in august absorb 0.53 t C/h of CO2 from atmosphere.•Algal biomass would increase with high pCO2 over a threshold (>13.56 µmol/L).•High CO2 condition can improve the nutrient-use efficiency of cyanobacteria.•High CO2 lead to the earlier occurrence of cyanobacterial bloom-maintenance phase. The effect of rising atmospheric CO2 on freshwater lakes is a subject of considerable debate. However, it is not clear how rising CO2 concentration affects cyanobacterial bloom development under potential nutrient limitation conditions and if CO2 should be taken into account in making nutrient reduction strategy. To fill the knowledge gaps, this study investigated the spatiotemporal variability in aquatic CO2 concentration (pCO2) from 2006 to 2016 in Lake Taihu, where cyanobacterial blooms often occurred from late spring to the early fall. Lake Taihu is an atmospheric CO2 source in May and November, with only 18% and 11% pCO2-undersaturated areas, respectively. During cyanobacterial bloom in August, 81% of the lake areas are pCO2-undersaturated, absorbing ~ 0.53 t C/h of atmospheric CO2. The results demonstrated that CO2 transfer across air-water interface was important in supporting cyanobacterial bloom development. Besides, Field investigation showed that the chlorophyll a level is significantly positively correlated with supersaturated pCO2 (>13.56 µmol/L) in May, but pCO2 decreases with high chlorophyll a levels in August, suggesting that cyanobacterial growth would be promoted by high pCO2 over a threshold. These observations suggested that the effect of rising atmospheric CO2 on freshwater lakes and cyanobacterial blooms should be paid attention to. Further, when the N- and P-levels are >0.3 mg/L and >0.02 mg/L, respectively, high-pCO2 conditions allow a more rapid growth rate of cyanobacteria via improved nutrient-use efficiency. Moreover, cyanobacteria afford maximum N- or P-use efficiency at lower N- or P-concentrations with high CO2 concentration. This improvement would result in an earlier bloom-maintenance phase and higher cyanobacterial biomass. In this case, nutrient reduction is more imperative under future high CO2 conditions. [Display omitted]